Producing and using video film : a tool for agricultural extension, a case study in Limpopo Province - Mphahlele, Chipientsho Koketso (My University, 2007)
The study was designed to outline the production process of a video film with farmers and its use as a tool for agricultural extension with other farmers engaged in similar development processes. The production process of the video film followed five stages namely: (1). Planning stage, where the production idea was discussed between the producer and the director. (2). Pre-production where brainstorming and conceptual framework were made. (3). Production stage was the shooting stage. Production took place at different venues with farmers and extension officers. (4). The editing stage using conceptual framework and Non Linear Editing (NLE) method to organize the video film into sequence; and (5) Distribution to project the video film with farmers in ten rural areas of the Limpopo province. Following the above-mentioned process, an eleven-minute film called Phanda na Vhulimi was produced with farmers, farmer’s leader as the main character and extension officers. Phanda na Vhulimi captured the farmer in her field, during meetings at various venues as a leader and during a public function in the village with provincial leaders. A back voice extensionist supplements the visual information with a description of the support process. In the ten villages the video film Phanda na Vhulimi was then projected to farmers following the subsequent steps: (1) Preparation for projection was a stage for arranging projection venues and setting sound to audible volume. (2) Pre-projection, here the researcher made a short presentation about the study without disclosing the content of the video film. (3) Projection was a stage of playing the video without pausing or talking by the projecting person (researcher) with exception to the viewers. (4) Post projection stage iii was where the video film was discussed with farmers, during this stage the researcher was acting as the facilitator to bring in farmer-to-farmer experience in relation to what was portrayed. After projections, an open-ended questionnaire was used to conduct this research. The raw data collected were analyzed by dividing it into two themes. The themes were divided into subsections as follows: preparation of the video film, reflection by the viewers/participants of the video film and learning during the projection process. The results of the study indicated that people in rural areas of South Africa watch television. There is a culture of shooting still pictures and watching video films but not hiring as they find it expensive, as a result, they borrow or watch with neighbours, friends i.e. other villages or watch family videos produced during special events. With this culture people are used to see pictures-both moving and still, therefore they will criticize less good quality pictures when they come across them. The study discovered that when a video film is produced with characters of the same background targeted audiences associate themselves with the product and feel that it represents them and their activities. These video films can be used as a tool to compliment not to replace the available methods of presentations.
Thesis (M.Sc. (Agriculture)) --University of Limpopo, 2007
Keywords: Agricultural extension; Agriculture -- Study and teaching -- Audio-visual aids; Agricultural extension work -- SOuth Africa -- Limpopo